Contentious Da’wah: Response Towards the Spreading of Puritan Islamic Movement - Jinan, Mutohharun; Sudarno, Sudarno (Prosiding University Research Colloquium, 2019)
This articleexamines the development of the puritan Islamic movement at Surakarta mainly is Majelis Tafsir Al-Quran (MTA). MTA is one of religious movement in Indonesia that is developed at villages area. When this movement is developing into various regions, then there tends to be conflict. The first purpose of this research is how do Muslims respond to the expansion of MTA in various regions. Second, what are the efforts taken by its members to maintain their existence and continue their missions to be accepted by the community. Even though get refusing but this movement is still survive. There are four kinds of responds towards da’wah by MTA, mainly; accommodative, critical, resistant, and conflict. MTA as the minority movement doing effort, interaction andbuild up social relationship anddefend itself through many ways, such as; inside ideology strengthening, enlarging the link of majority movement leaders, doing social jobs, leading law enforcement in completing problem.The various ways taken by the puritan Islamic movement are still incomplete to build good relations, and are still considered to cause problems in the society. The spreading of puritan Islamic movement as a contentious da’wah.